Land use strongly influences soil organic carbon and bacterial community export in runoff in tropical uplands - Le, Huong T.; Rochelle‐Newall, Emma; Ribolzi, Olivier; Janeau, Jean Louis; Huon, Sylvain; Latsachack, Keooudone; Pommier, Thomas (Land degradation & development, 2020)
Rapid development and associated land‐use change have resulted in increased soil erosion and widespread land degradation in tropical ecosystems. Precipitation‐induced soil erosion causes the export of soil organic carbon (SOC) and the associated bacterial community affecting soil quality and functioning. We assessed the transfer of SOC and soil bacterial diversity and functions in surface water runoff from different land uses: Teak with and without understory (TW and TWO, respectively) and upland rice (UR) in a tropical, upland catchment during a simulated rain event. Total suspended sediment (TSS) concentration was higher in TWO (1.23 ± 0.21 g L−1) than in TW (0.37 ± 0.16 g L−1) and UR (0.44 ± 0.2 g L−1), whereas dissolved organic carbon (DOC) concentration was lower under TWO (3.8 ± 0.7 mg L−1) than under TW or UR (13.4 ± 7.5 and 9.57 ± 4.8 mg L−1, respectively). Runoff from TWO harboured the highest proportion of bacterial taxa common to soil (27% and 29.5%) as compared with TW (22.8% and 13%) and UR (17.3% and 7%) for both particle attached and free‐living fractions, respectively. Bacterial community export in surface runoff was driven by changes in DOC and TSS, suggesting that eroded soil particles simultaneously carry organic carbon and attached bacterial taxa in surface runoff. Consequently, the export of soil functional groups relating to organic carbon degradation and nitrogen cycle was higher under TWO than in TW or UR. Our results underline that teak plantations with unsustainable practices such as the removal of understory degrades soil functions and accelerates land degradation through soil erosion and surface runoff on the long term.